Identifikasi Permasalahan Dalam Penerapan Model Creative Problem Solving Berbasis Moodle di SMP - Dina Syaflita; Sari Aini; Ria Rizkia Alvi; Fekie Adila (Universitas Indraprasta PGRI Jakarta, 2023)
Creative Problem Solving (CPS) model is a model that supports students to develop creative thinking skills. However, this model is still not widely used in classroom learning, especially junior high school. Therefore, in its application, there is a possibility that the teacher will experience several obstacles which become in the implementation of increasing students' creative thinking skills using this model. This type of research is descriptive research. The object of this research is class VII.1 for the 2022/2023 academic year. Data collection techniques were obtained from observation, interviews, and student responses in writing regarding the constraints during the use of the Moodle-assisted CPS model on temperature and heat material at SMPN 1 Perhentian Raja. The obstacles encountered in the implementation of this research were 1) the initial use of Moodle which may be new to most students, so it needs to be introduced first, 2) in the first learning activity, junior high school students still had difficulty identifying what was the problem in the reading material presented 3) at the beginning of the activity students tend to provide at most 2 solutions, the teacher needs to provide a stimulus so that students can think more creatively to produce more ideas, 4) not all learning processes can be completed within 2 JP so it is necessary to consider the problems presented or additional time allotted.